Gender and intraoperative blood transfusion: analysis of 54, 122 non-reoperative coronary revascularization procedures. (April 2019) - Stammers, Alfred H.; Tesdahl, Eric A.; Mongero, Linda B.; Stasko, Andrew
Background: Previous studies have shown that women undergoing isolated coronary artery bypass graft (CABG) surgery have an increased risk for postoperative morbidity and mortality when compared to men. Additionally, recent evidence suggests that blood transfusions are independently associated with an increased risk of adverse outcome. Methods: We evaluated gender differences in the risk of intraoperative red blood cell (RBC) transfusion during CABG surgery. Consecutive, non-reoperative CABG procedures performed across 196 institutions between April 2012 and May 2015 were retrospectively reviewed. Gender differences for intraoperative transfusion were evaluated with a multi-variable binary logistic regression model, adjusting for age, blood volume (Nadler formula to normalize for height and weight), body mass index, procedure acuity, net extracorporeal circuit prime volume, use of autologous priming, first hematocrit (Hct) in the operating room (OR), nadir Hct on cardiopulmonary bypass (CPB), volume added on CPB, ultrafiltration volume, urine output on CPB and procedure duration. Results: Among 54, 122 patients (25.3% female), 21.6% (n = 11, 701) received a RBC transfusion. Compared to men, female patients were older (66 years vs. 64 years, p<0.001), had lower blood volumes (4.3L vs. 5.6L, p<0.001) and a lower preoperative Hct (32.9% vs. 37.2%, p<0.001). Transfusion rates were three-fold higher in women versus men (45.1% vs. 13.7%, p<0.001). After adjustment for independent predictors of intraoperative transfusion, women remained at increased risk versus men (OR = 1.30, 95%CI = 1.19−1.43). Conclusions: Women have an increased risk of intraoperative RBC transfusion versus men. After adjusting for height and weight, much of this risk is due to gender differences in preoperative Hct and blood volume; however, a residual significant risk remained after adjustment. Perfusion strategies aimed at gender differences may minimize unnecessary transfusions. Future study on the impact of gender on transfusion practice in cardiac surgery is warranted.